Model based simulation for a smartcity project based on LoRa - Mesquita, Rui (2019)
The ”SmartCity: Lagoa” project is a partnership within the ”Portugal 2020” project, a municipality-scale installation of 20,000 IoT devices over the next 3 years. These devices include sensors for temperature, humidity, luminosity, volumetry, noise, carbon monoxide, pH, and ORP, among others; all transmitting the collected data to one of six gateways using LoRa technology. In the implementation of this project, a lack of tools allowing the simulation of LoRa based projects was detected. This paper presents a framework to simulate and monitor a project based on LoRa, using a precise and executable graphical language. The simulation can use, as input, real data from the implemented system and other data added for simulation purposes. This allows a basis on reality introducing useful information to guide the simulation to the intended tests. The behaviors are defined using CPN Tools, a design environment allowing editing, simulation, and verification of high-level Petri net models. This paper presents the system design and how the executable models were used to simulate and validate the model, namely the system behavior when gateways and sensors are connected and disconnected.